Importance of Human Breast Milk in the Early Colonization of Streptococcus mutans - Cordova-Carrillo, Karina; De La Peña Lobato, Cristina; CUEVAS-GONZALEZ, MARIA VERONICA; Cuevas-González, Juan Carlos; Espinosa Cristobal, Leon Francisco; Tovar Carrillo, Karla Lizette; Saucedo Acuña, Rosa Alicia; Reyes-López, Simón Yobanny; Zambrano-Galvan, Graciela (2024)
Background and objectives: The development of the oral microbiome begins in the prenatal stage. Breast milk contains antimicrobial proteins, microorganisms, metabolites, enzymes, and immunoglobulins, among others; therefore, differences have been noted in the type of microorganisms that colonize the oral cavity of children who are breastfed compared to those who are formula-fed. Our objective was to establish the relationship between breastfeeding, formula feeding, or mixed feeding (breastfeeding and formula) with the presence of S. mutans in a population of children under 6 months of age. Materials and Methods: The patients were recruited from the Child Care Center of Ciudad Juárez, Chihuahua, and from the pediatric dentistry postgraduate clinics of the Autonomous University of Ciudad Juárez; children exclusively fed maternally, with formula, and/or mixed were included. Those who had been fed within the previous hour were excluded. The sample was taken with a smear of the jugal groove using a sterile micro-brush. For the identification of Streptococcus mutans, a culture of Mitis Salivarius Agar (Millipore) was used. Results: 53.3% corresponded to females and 46.7% to males, 36.7% corresponded to maternal feeding, 23.3% corresponded to formula feeding, and 40% corresponded to mixed feeding. In 90% of the infants, the parents indicated that they did not perform oral hygiene. The CFU count showed that infants who were exclusively breastfed had an average of 9 × 10 CF/mL, formula-fed infants had an average of 78 × 10 CFU/mL, and those who had mixed feeding 21 × 10 CFU/mL. Conclusions: According to the results obtained, it was possible to corroborate that exclusive breastfeeding limits the colonization of Streptococcus mutans compared to those infants who receive formula or mixed feeding; these results could have a clinical impact on the dental health of infants by having a lower presence of one of the main etiological factors involved in dental caries and the type of microbiome established in the oral cavity.